2019
DOI: 10.1071/an17637
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy X-ray absorptiometry is a valid tool for assessing in vivo body composition of broilers

Abstract: The use of non-invasive techniques to estimate body composition in animals in vivo conforms to the desire to improve the welfare of animals during research and also has the potential to advance scientific research. The purpose of the present study was to determine a predictive equation of the dual energy X-ray absorptiometry (DXA) method for broilers by comparing the measurement of body composition using DXA with that by chemical analysis. In total, 720 day-old Cobb500 broilers were distributed into a split-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
7
8
0
Order By: Relevance
“…In agreement with the present results, the feasibility of DXA technology in assessing carcass composition has been stated for broiler chickens [ 13 ], pigs [ 15 ], and sheep [ 14 ], and good R 2 values have also been described for calves [ 16 , 18 ]. Aligning with our results, in all these studies, higher R 2 values were described for total fat and total lean estimations than for total bone estimations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with the present results, the feasibility of DXA technology in assessing carcass composition has been stated for broiler chickens [ 13 ], pigs [ 15 ], and sheep [ 14 ], and good R 2 values have also been described for calves [ 16 , 18 ]. Aligning with our results, in all these studies, higher R 2 values were described for total fat and total lean estimations than for total bone estimations.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Dual-energy X-ray absorptiometry (DXA) technology is a promising indirect method to estimate carcass composition due to its relatively low cost, high reliability of data collection, and ease of use [ 5 ]. In the literature, the feasibility, accuracy, and precision of DXA technology has been reported on salmon [ 12 ], broiler chickens [ 13 ], sheep [ 14 ], swine [ 15 ], and cattle [ 16 ]. In addition, Soladoye et al [ 15 ], Kipper et al [ 17 ], and López-Campos et al [ 18 ] assessed the accuracy of DXA technology on mass measurement of primal cuts from pigs and steers.…”
Section: Introductionmentioning
confidence: 99%
“…After FHP measurements, lean mass (protein, water, and solute contents), lipid mass, and bone mineral content were analyzed for each bird in vivo using dual-energy X-ray absorptiometry (DEXA). The DEXA scanning procedure was done according to the validated procedure reported by Gonç alves et al [15]. The relative weight was expressed in grams of component per kilo of body weight.…”
Section: Body Composition Analysesmentioning
confidence: 99%
“…Although carcass chemical analysis produces reliable measurements, it does not allow for repeated measurements on the same animal throughout its growth, which is feasible with live animal methods. Furthermore, live animal methods meet the ethical demands of certain groups of society for animal care and use, by preventing slaughter of several individuals; moreover, this method can reduce costs and environmental pollution associated with chemical analysis ( Gonçalves et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, DEXA needs to be calibrated to estimate the body composition of birds because the technique is not capable of directly estimating protein and water contents. Some works have shown that DEXA is effective at estimating body composition of chickens by comparing DEXA results with chemical analysis ( Mitchell et al, 1997 ; Swennen et al, 2004 ; Salas et al, 2012 ; Gonçalves et al, 2018 ; Schallier et al, 2019 ). According to Mitchell et al (2011) , chicken feathers are not detected by DEXA.…”
Section: Introductionmentioning
confidence: 99%